The Discourse of Drama: Regulating Girls in an Icelandic School. Issue 3 (1st December 2021) - Thrastardóttir, Bergljót; Lárusdóttir, Steinunn Helga; Ásgeir Jóhannesson, Ingólfur
Abstract: In this article, we consider how girls are positioned in school by what we have chosen to call the discourse of drama. The widely held notion that Nordic girls have it all along with this drama discourse are seen to be the key narratives that reinforce a hegemonic form of girlhood. This ethnographic study focuses on the relations of students between the ages of 13 and 15 in the light of uninformed school staff-member practices. Our findings suggest that girls, despite living in what is seen to be a country that upholds gender equality, are silenced through this discourse of drama. We suggest that teacher education should lead to the facilitation of a gender-inclusive school environment free of stereotypical ideas of gender as a fixed binary.